Bridging the academic–industrial gap: application of an oxygen and pH sensor-integrated lab-on-a-chip in nanotoxicology. Issue 21 (4th October 2021) - Zirath, Helene; Spitz, Sarah; Roth, Doris; Schellhorn, Tobias; Rothbauer, Mario; Müller, Bernhard; Walch, Manuel; Kaur, Jatinder; Wörle, Alexander; Kohl, Yvonne; Mayr, Torsten; Ertl, Peter
Abstract : A dual-sensor integrated microfluidic cell analysis platform for the non-invasive and time-resolved monitoring of cellular oxygen uptake and metabolic activity (pH) in the context of nanotoxicological risk assessment. Abstract : Translation of advanced cell-based assays exhibiting a higher degree of automation, miniaturization, and integration of complementary sensing functions is mainly limited by the development of industrial-relevant prototypes that can be readily produced in larger volumes. Despite the increasing number of academic publications in recent years, the manufacturability of these microfluidic cell cultures systems is largely ignored, thus severely restricting their implementation in routine toxicological applications. We have developed a dual-sensor integrated microfluidic cell analysis platform using industrial specifications, materials, and fabrication methods to conduct risk assessment studies of engineered nanoparticles to overcome this academic–industrial gap. Non-invasive and time-resolved monitoring of cellular oxygen uptake and metabolic activity (pH) in the absence and presence of nanoparticle exposure is accomplished by integrating optical sensor spots into a cyclic olefin copolymer (COC)-based microfluidic platform. Results of our nanotoxicological study, including two physiological cell barriers that are essential in the protection from exogenous factors, the intestine (Caco-2) and the vasculature (HUVECs) showed that the assessment of the cells' total energy metabolism is ideally suited to rapidly detect cytotoxicities. Additional viability assay verification using state-of-the-art dye exclusion assays for nanotoxicology demonstrated the similarity and comparability of our results, thus highlighting the benefits of employing a compact and cost-efficient microfluidic dual-sensor platform as a pre-screening tool in nanomaterial risk assessment and as a rapid quality control measure in medium to high-throughput settings.